METHOD OF SYSTEM ANALOG CONTROL FOR OF MULTI-ROAD ROUTING IN COMPLEX COMPUTER SYSTEMS - Baranov , G. L.; Zhukov, I. A.; Martinova, O. P.; Baranov, V. L. (Problems of Informatization and Management, 2021)
The method of system-alarm control is described, which is based on the concept of system-analog modeling of complex systems. It is shown that the method of system-analog control provides an increase in the speed of solving the problem of multi-path routing in complex computer systems.